KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENDUKUNG GERAKAN LITERASI SEKOLAH - Asmawan, Moh Chairil (Jurnal Pendidikan Ilmu Sosial, 2018)
This article explores descriptively by using literature review about transformational leadership and the principal strategy to support literacy movement in school. The study found that the critical roles of principal strategy to support financial movement are: (1) developing the curriculum that strengthen science knowledge, nature of science, and implementation in technology and the impacts to the environment and society; (2) incorporating with society (parents, committee, and alumni) for providing books in library; (3) using contextual learning strategy that balancing learning activity in school and society; (4) Strengthen story telling activity or re-telling to motivate students to read; (5) arranging pedagogic approach included discussion, scientific research, academic writing, and argumentation; (6) recruit professional library officer; (7) encourage teacher and staff to supportÂ  school literacy movement with 15 minutes reading before learning starts; (8) developing short and long term literacy program.